Improving Students’ Vocabulary through Make a Match Method at Class VIII of Mts al-Khairiyah Kubangsari - Reni Raudatul Munawaroh; Ahmad Suhaili (Loquen, 2017)
Abstract: The objective of this research is to improve students’ vocabulary through make a match method students at Class VIII MTs Al-Khairiyah Kubangsari. This school located on JL. Sunan Bonang, Lk. Penauan RT 02 RW 01, Kelurahan Kubangsari, Kecamatan Ciwandan, Kota Cilegon Provinsi Banten, 42445. The research was held in February 2018. The researcher conducted two cycles about improve students’ vocabulary through make a match method, students’ at Class VIII A MTs Al-Khairiyah Kubangsari in the second semester of the academic year 2017/2018. The total of the students were 21 students. The research that was done Classroom Action Research. It was done in two cycle and each step has four steps. They were planning, action, observing, and reflecting. Result of the researcher’s observation in the class when teaching learning process, there were students’ improvement in cycle II. Students could study enthusiast. The students got better scores in the second cycle than first cycle. The students score in cycle I was 67.14 and the score in cycle II was 81.90 while in improvement of students average score in cycle I and II was 14.76. Based on this result, it can be concluded that make a match method can improve students’ vocabulary at class VIII A Mts Al-Khairiyah Kubangsari. It means that make a match method can make the students easier to understand the text and more convenient and pleasant to study in teaching learning, students can be better in their vocabulary. Keywords: Vocabulary, Make a match method, and Classroom Action Research. Abstract: The objective of this research is to improve students’ vocabulary through make a match method students at Class VIII MTs Al-Khairiyah Kubangsari. This school located on JL. Sunan Bonang, Lk. Penauan RT 02 RW 01, Kelurahan Kubangsari, Kecamatan Ciwandan, Kota Cilegon Provinsi Banten, 42445. The research was held in February 2018. The researcher conducted two cycles about improve students’ vocabulary through make a match method, students’ at Class VIII A MTs Al-Khairiyah Kubangsari in the second semester of the academic year 2017/2018. The total of the students were 21 students. The research that was done Classroom Action Research. It was done in two cycle and each step has four steps. They were planning, action, observing, and reflecting. Result of the researcher’s observation in the class when teaching learning process, there were students’ improvement in cycle II. Students could study enthusiast. The students got better scores in the second cycle than first cycle. The students score in cycle I was 67.14 and the score in cycle II was 81.90 while in improvement of students average score in cycle I and II was 14.76. Based on this result, it can be concluded that make a match method can improve students’ vocabulary at class VIII A Mts Al-Khairiyah Kubangsari. It means that make a match method can make the students easier to understand the text and more convenient and pleasant to study in teaching learning, students can be better in their vocabulary.